FKUB DIALOGICAL COMMUNICATION IN DEVELOPING RELIGIOUS TOLERANCE IN THE CITY OF SURAKARTA - Riyanto, Buddy (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The background of this research is the emergence of religious radicalism and intolerant behavior by some groups of people in various parts of Indonesia, including Surakarta, which, if not addressed immediately, can threaten harmonious social life in the society. The Religious Harmony Forum (FKUB) was formed by the Ministry of Religion whose main objective is to established harmony between religious communities, to foster religious tolerance. One of its main tasks is to carry out dialogue with religious and community leaders. The purpose of this study was to describe the dialogical communication process carried out by the Surakarta FKUB with these religious and community leaders. Referring to the constructivist paradigm, this study uses qualitative methods. This study concluded that dialogical communication carried out by FKUB Surakarta was quite effective in overcoming differences, could prevent radicalism and lead to tolerant understanding, attitudes and behavior among the Surakarta community. Keywords: dialogical communication, FKUB, religious tolerance.